CÁLCULO POR EL MÉTODO MONTE CARLO DE UN 6°Co DE TERAPIA UTILIZANDO EL CÓDIGO FOTELP - Ramos P., N. (2005)
In this work the simulation is presented by means of the method Monte Cario Utilizing the code FOTELP, simulating a 60Co of therapy for the purpose of obtaining dose percentage curves in depth (PDD), for a seze of field of lOxlO cm2, for such motive I am built the virtual headrest ofthe cobalt and for the deposition ofthe dose of water I am built a fantoma virtual with dimensions of 30x30x30 cm3 • Said results were compared with theoretical data, being obtained thus an acceptable result.